Exogenous Rinolith: a case report - I Putu Santhi Dewantara; Luh Made Ratnawati (DiscoverSys Inc., 2020)
Background: Rhinolith results from mineralized nasal foreign bodies. The time required for rhinolith formation is around 15 years and is usually diagnosed in the third decade of life. Most rhinoliths are asymptomatic or present with unspecific minimal symptoms. Symptoms of rhinolith include unilateral or bilateral foul nasal discharge, epistaxis, nasal obstruction, and halitosis. This case study aims to evaluate the recent management of exogenous rhinolith.Case Presentation: We present a case of unilateral rhinolith in an 11 years old boy with a history of inserting eraser fragment into the left nostril at the age of 5. The patient complained of recurrent epistaxis with foul nasal discharge from the left nasal cavity. Rhinolith was extracted under general anesthesia. The extraction performed using raspatorium and headlight. The rhinolith was firmly attached to the floor of the nasal cavity but can be removed in toto. The specimen was sent to the Pathology Department for histopathological examination. The result showed respiratory epithelium covering edematous stroma with a proliferative vessel and lymphoplasmacytic inflammatory cell infiltrationConclusion: Rhinolith is a rare condition with no or minimal symptoms. Management of rhinolith is extraction that can be performed under local or general anesthesia.